Biologic Association Annual Summit: 2020 Report. Issue 6 (4th June 2021) - Frank, Rachel M.; Sherman, Seth L.; Chahla, Jorge; Dragoo, Jason L.; Mandelbaum, Bert; ,; Anz, Adam W.; Bradley, James P.; Chu, Constance R.; Cole, Brian J.; Farr, Jack; Flanigan, David C.; et al.
Interest and research in biologic approaches for tissue healing are exponentially growing for a variety of musculoskeletal conditions. The recent hype concerning musculoskeletal biological therapies (including viscosupplementation, platelet-rich plasma, and cellular therapies, or "stem cells") is driven by several factors, including demand by patients promising regenerative evidence supported by substantial basic and translational work, as well as commercial endeavors that complicate the scientific and lay understanding of biological therapy outcomes. While significant improvements have been made in the field, further basic and preclinical research and well-designed randomized clinical trials are needed to better elucidate the optimal indications, processing techniques, delivery, and outcome assessment. Furthermore, biologic treatments may have potential devastating complications when proper methods or techniques are ignored. For these reasons, an association comprising several scientific societies, named the Biologic Association (BA), was created to foster coordinated efforts and speak with a unified voice, advocating for the responsible use of biologics in the musculoskeletal environment in clinical practice, spearheading the development of standards for treatment and outcomes assessment, and reporting on the safety and efficacy of biologic interventions. This article will introduce the BA and its purpose, provide a summary of the 2020 first annual Biologic Association Summit, and outline the future strategic plan for the BA.